A high-conductivity lithium phosphate sputtering target for solid-state battery field and preparation method thereof
By mixing lithium phosphate powder with modified lithium phosphate powder and calcining materials, combining magnetic graphene oxide as adhesive, the conductive performance of solid-state battery targets is improved, and the problem of insufficient conductive performance in the existing technology is solved, so as to achieve The preparation of highly conductive lithium phosphate targets is suitable for solid-state batteries.
Patent Information
- Application Number
- CN202411464788.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-21
AI Technical Summary
In the prior art, the conductivity of lithium phosphate targets still needs to be further improved after sputtering to meet the application needs of solid-state batteries.
By mixing lithium phosphate powder, modified lithium phosphate powder, niobium oxide powder, titanium oxide powder, and zirconia powder, ball milling and calcining, a highly conductive composite powder is formed and pressed into a mold, and magnetic graphene oxide is used as the Adhesives to improve conductivity.
It significantly improves the density and conductivity of the target material, ensures the high conductivity of the film after sputtering, and is suitable for solid-state battery fields.
Smart Images

Figure CN118955116B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of target materials and target material manufacturing, and in particular to a high-conductivity lithium phosphate sputtering target material for solid-state batteries and a preparation method thereof. Background Art
[0002] The rapid development of miniaturization of electronic devices such as sensors requires a small, light, and high-capacity micro-compact power source to match it. All-solid-state thin-film lithium-ion batteries have received extensive attention at home and abroad in recent years due to their high power density, low self-discharge rate, excellent charge and discharge cycle performance, arbitrary design of shape and size, no solution leakage, no explosion, and safe use. Some countries have achieved industrial production. This type of battery can be used as an independent or backup power source for various portable microelectronic devices, showing broad application prospects both in civilian and military applications.
[0003] Lithium phosphate is the most stable and widely used solid electrolyte in solid-state thin-film batteries. Its preparation is the key to all-solid-state thin-film batteries, and the corresponding film performance directly determines the capacity and performance of the battery. Therefore, the quality of the target material is also particularly important.
[0004] Patent document CN114057480B discloses a lithium phosphate solid electrolyte target material and preparation method for preparing thin-film lithium batteries. Based on the lithium phosphate solid electrolyte target material and magnetron sputtering coating technology prepared by the present invention, the contact surface resistance of the prepared all-solid-state thin-film lithium battery is significantly reduced, which significantly improves the performance of the battery. Patent document CN116253570B discloses a preparation method and application of a LiPON target material and thin film. The thin film obtained by sputtering the target material has higher ionic conductivity than the existing electrolyte film.
[0005] Although the above patents have improved the conductivity of lithium phosphate targets to a certain extent, the conductivity of the targets still needs to be further improved when applied to solid-state batteries after sputtering. Summary of the invention
[0006] In view of this, the purpose of the present invention is to propose a high-conductivity lithium phosphate sputtering target material and a preparation method thereof for use in the field of solid-state batteries, so as to provide a high-conductivity lithium phosphate sputtering target material, and the thin film obtained after sputtering of the target material can meet the application in the field of solid-state batteries.
[0007] Based on the above purpose, the present invention provides a method for preparing a high-conductivity lithium phosphate sputtering target for solid-state batteries, characterized in that it comprises the following steps:
[0008] (1) mixing lithium phosphate powder, modified lithium phosphate powder, niobium oxide powder, titanium oxide powder and zirconium oxide powder, and performing a ball milling process to obtain a mixed powder;
[0009] (2) calcining the mixed powder at 300-600°C for 2-4h, performing secondary ball milling, and sieving to obtain a composite powder;
[0010] (3) The composite powder is loaded into a mold, pressed into shape, and then sintered to obtain a highly conductive lithium phosphate sputtering target for solid-state batteries;
[0011] The preparation steps of the modified lithium phosphate powder in step (1) are as follows:
[0012] S1: dissolving graphene oxide in ethanol, and obtaining a graphene oxide dispersion after ultrasonic homogenization, then adding ferric chloride hexahydrate, sodium acrylate, and sodium acetate, stirring evenly, reacting at 180-220°C for 20-24h, and obtaining magnetic graphene oxide after purification;
[0013] S2: Dissolve the magnetic graphene oxide in ethanol, and obtain a magnetic graphene oxide dispersion after ultrasonic homogenization. Then add a lithium source and a phosphorus source, dilute with water, and after ultrasonic dispersion, transfer the obtained solution into a polytetrafluoroethylene reactor, react at 180-200°C for 15-18 h, centrifuge, filter, wash, dry, sinter, and crush to obtain a modified lithium phosphate powder;
[0014] Preferably, in step S1, the weight ratio of graphene oxide, ferric chloride hexahydrate, sodium acrylate and sodium acetate is 2-3:20-30:10-15:30-50.
[0015] Preferably, in step S2, the weight ratio of the magnetic graphene oxide, the phosphorus source and the lithium source is 2-2.5:0.7-0.8:1.15-1.2.
[0016] Preferably, the phosphorus source in step S2 is H 3 PO 4 and NH 4 H 2 PO 4 One of them.
[0017] Preferably, the lithium source in step S2 is LiOH and Li 3 PO 4 One of them.
[0018] Preferably, the sintering in step S2 is carried out in an argon atmosphere at 400-900° C. for 8-10 hours.
[0019] Preferably, the specific surface area of the lithium phosphate powder in step (1) is 5-15 m 2 / g, the specific surface area of niobium oxide powder is 10-30m 2 / g, the specific surface area of zirconia powder is 2-10m 2 / g, the specific surface area of titanium oxide powder is 10-20m 2 / g.
[0020] Preferably, the ball milling speed of the first ball milling in step (1) is 400-600 rpm, and the ball milling time is 6-8 h.
[0021] Preferably, the weight percentages of the lithium phosphate powder, modified lithium phosphate powder, niobium oxide powder, titanium oxide powder and zirconium oxide powder in step (1) are 91%-97.91%: 2%-3%: 0.03%-2%: 0.03%-2%: 0.03%-2%.
[0022] Preferably, the ball milling speed of the secondary ball milling in step (2) is 100-200 rpm, and the ball milling time is 3-5 h.
[0023] Preferably, the particle size of the composite powder after sieving in step (2) is 30-50 μm.
[0024] Preferably, the pressure of the pressing molding in step (3) is 5-20 MPa.
[0025] Preferably, the sintering in step (3) is carried out under vacuum degree <100pa, 500-950°C, 1-10Mpa, and heat and pressure maintenance for 2-3h.
[0026] Furthermore, the present invention also provides a high-conductivity lithium phosphate sputtering target for use in the field of solid-state batteries, which is prepared by the above-mentioned method for preparing a high-conductivity lithium phosphate sputtering target for use in the field of solid-state batteries.
[0027] Beneficial effects of the present invention:
[0028] (1) The present invention mixes magnetic graphene oxide with raw materials by doping, which can make the magnetic graphene oxide more evenly dispersed, form a more uniform conductive network, and form a more stable interface bonding, thereby improving the density and conductive properties of the target material.
[0029] (2) The present invention adds magnetic graphene oxide to the raw materials. Magnetic graphene oxide has excellent electrical conductivity and magnetism, and can be used as a binder to improve the sphericity of the composite powder, while also greatly improving the density and electrical conductivity of the target material.
[0030] (3) After the mixed powder is calcined, the magnetic graphene oxide doped between the raw materials can act as a binder, so that the raw material powders are more tightly and stably bonded, the sphericity of the composite powder is improved, and the density of the target material is further improved.
[0031] (4) The present invention dopes magnetic graphene oxide into the raw material and then performs calcination, thereby improving the sphericity of the composite powder and further improving the density and conductivity of the target material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art description.
[0033] Figure 1 This is a scanning electron microscope image of the target material obtained in Example 2 of the present invention;
[0034] Figure 2 This is a scanning electron microscope image of the composite powder obtained during the preparation process of Example 2 of the present invention;
[0035] Figure 3 This is the element energy spectrum distribution diagram of the target material obtained in Example 2 of the present invention. DETAILED DESCRIPTION
[0036] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0037] Embodiment 1:
[0038] A highly conductive lithium phosphate sputtering target for solid-state batteries, the specific preparation process is as follows:
[0039] (1) Dissolve 2 g of graphene oxide in 500 ml of ethanol, and obtain a graphene oxide dispersion after ultrasonic homogenization. Then add 20 g of ferric chloride hexahydrate, 10 g of sodium acrylate, and 30 g of sodium acetate. After stirring evenly, react at 180 ° C for 20 h, centrifuge, filter, wash, and dry to obtain magnetic graphene oxide;
[0040] (2) 2 g of magnetic graphene oxide was dissolved in 700 ml of ethanol and homogenized by ultrasonication to obtain a magnetic graphene oxide dispersion. Then, 0.7 g of LiOH and 1.15 g of NH 4 H 2 PO 4 , dilute with water, after ultrasonic dispersion, transfer the obtained solution into a polytetrafluoroethylene reactor, react at 180 ° C for 15 h, centrifuge, filter, wash, freeze-dry, keep warm at 400 ° C for 8 h in an argon atmosphere, and then pulverize to obtain modified lithium phosphate powder;
[0041] (3) 91 g of lithium phosphate powder, 3 g of modified lithium phosphate powder, 2 g of niobium oxide powder, 2 g of titanium oxide powder, and 2 g of zirconium oxide powder were mixed and ball-milled at 400 rpm for 6 h to obtain a mixed powder;
[0042] (4) calcining the mixed powder at 300 °C for 2 h, then ball milling at 100 rpm for 3 h, sieving to obtain a composite powder with a particle size of 30-50 μm;
[0043] (5) The composite powder is loaded into a mold and first pressed at 5 MPa, and then kept warm and pressurized at a vacuum degree of less than 100 Pa, 500 ° C, and 1 MPa for 8 hours to obtain a high-conductivity lithium phosphate sputtering target for the solid-state battery field.
[0044] Embodiment 2:
[0045] A highly conductive lithium phosphate sputtering target for solid-state batteries, the specific preparation process is as follows:
[0046] (1) Dissolve 2.5 g of graphene oxide in 500 ml of ethanol, and after ultrasonic homogenization, obtain a graphene oxide dispersion. Then add 25 g of ferric chloride hexahydrate, 13 g of sodium acrylate, and 40 g of sodium acetate. After stirring evenly, react at 200 ° C for 22 h, centrifuge, filter, wash, and dry to obtain magnetic graphene oxide.
[0047] (2) 2.3 g of magnetic graphene oxide was dissolved in 700 ml of ethanol and homogenized by ultrasonication to obtain a magnetic graphene oxide dispersion. Then, 0.75 g of LiOH and 1.2 g of NH 4 H 2 PO 4 , diluted with water, after ultrasonic dispersion, the obtained solution was transferred into a polytetrafluoroethylene reactor, reacted at 190°C for 17 h, centrifuged, filtered, washed, freeze-dried, kept warm at 700°C in an argon atmosphere for 9 h, and crushed to obtain modified lithium phosphate powder;
[0048] (3) 94.5 g of lithium phosphate powder, 2.5 g of modified lithium phosphate powder, 1 g of niobium oxide powder, 1 g of titanium oxide powder, and 1 g of zirconium oxide powder were mixed and ball-milled at 500 rpm for 7 h to obtain a mixed powder;
[0049] (4) calcining the mixed powder at 450 °C for 3 h, then ball milling at 150 rpm for 4 h, sieving to obtain a composite powder with a particle size of 30-50 μm;
[0050] (5) The composite powder is loaded into a mold and first pressed at 15 MPa, and then kept warm and pressurized at a vacuum degree of less than 100 Pa, 750 ° C, and 8 MPa for 9 hours to obtain a high-conductivity lithium phosphate sputtering target for the solid-state battery field.
[0051] Embodiment 3:
[0052] A highly conductive lithium phosphate sputtering target for solid-state batteries, the specific preparation process is as follows:
[0053] (1) 3 g of graphene oxide was dissolved in 500 ml of ethanol, and after ultrasonic homogenization, a graphene oxide dispersion was obtained. Subsequently, 30 g of ferric chloride hexahydrate, 15 g of sodium acrylate, and 50 g of sodium acetate were added, and after stirring, the mixture was reacted at 220 ° C for 24 h, and then centrifuged, filtered, washed, and dried to obtain magnetic graphene oxide;
[0054] (2) Dissolve 2.5 g of magnetic graphene oxide in 700 ml of ethanol and mix them by ultrasonication to obtain a magnetic graphene oxide dispersion. Then, add 0.8 g of LiOH and 1.2 g of NH 4 H 2 PO 4 , dilute with water, after ultrasonic dispersion, transfer the obtained solution into a polytetrafluoroethylene reactor, react at 200 ° C for 18 h, centrifuge, filter, wash, freeze-dry, keep warm at 900 ° C for 10 h in an argon atmosphere, and then crush to obtain modified lithium phosphate powder;
[0055] (3) 97.91 g of lithium phosphate powder, 3 g of modified lithium phosphate powder, 0.03 g of niobium oxide powder, 0.03 g of titanium oxide powder, and 0.03 g of zirconium oxide powder were mixed and ball-milled at 600 rpm for 8 h to obtain a mixed powder;
[0056] (4) calcining the mixed powder at 600 °C for 4 h, then ball milling at 200 rpm for 5 h, sieving to obtain a composite powder with a particle size of 30-50 μm;
[0057] (5) The composite powder is loaded into a mold and first pressed at 20 MPa, and then kept warm and pressurized at a vacuum degree of less than 100 Pa, 950 ° C, and 10 MPa for 10 hours to obtain a high-conductivity lithium phosphate sputtering target for the solid-state battery field.
[0058] Comparative Example 1:
[0059] A lithium phosphate sputtering target material, the specific preparation process is as follows:
[0060] The difference from Example 2 is that the magnetic graphene oxide is replaced by graphene oxide. The specific steps are as follows:
[0061] (1) 2.3 g of graphene oxide was dissolved in 700 ml of ethanol and homogenized by ultrasonication to obtain a graphene oxide dispersion. Then 0.75 g of LiOH and 1.2 g of NH 4 H 2 PO 4, diluted with water, after ultrasonic dispersion, the obtained solution was transferred into a polytetrafluoroethylene reactor, reacted at 190°C for 17 h, centrifuged, filtered, washed, freeze-dried, kept warm at 700°C in an argon atmosphere for 9 h, and crushed to obtain modified lithium phosphate powder;
[0062] (2) 94.5 g of lithium phosphate powder, 2.5 g of modified lithium phosphate powder, 1 g of niobium oxide powder, 1 g of titanium oxide powder, and 1 g of zirconium oxide powder were mixed and ball-milled at 500 rpm for 7 h to obtain a mixed powder;
[0063] (3) The mixed powder was calcined at 450 °C for 3 h, then ball-milled at 150 rpm for 4 h, and sieved to obtain a composite powder with a particle size of 30-50 μm;
[0064] (4) The composite powder is loaded into a mold and first pressed at 15 MPa, and then kept warm and pressurized at a vacuum degree of less than 100 Pa, 750 ° C, and 8 MPa for 9 hours to obtain a high-conductivity lithium phosphate sputtering target for the solid-state battery field.
[0065] Comparative Example 2:
[0066] A lithium phosphate sputtering target material, the specific preparation process is as follows:
[0067] The difference from Example 2 is that the magnetic graphene oxide is directly mixed with the raw material powder. The specific steps are as follows:
[0068] (1) Dissolve 2.5 g of graphene oxide in 500 ml of ethanol, and after ultrasonic homogenization, obtain a graphene oxide dispersion. Then add 25 g of ferric chloride hexahydrate, 13 g of sodium acrylate, and 40 g of sodium acetate. After stirring evenly, react at 200 ° C for 22 h, centrifuge, filter, wash, and dry to obtain magnetic graphene oxide.
[0069] (2) 94.5 g of lithium phosphate powder, 2.5 g of magnetic graphene oxide, 1 g of niobium oxide powder, 1 g of titanium oxide powder, and 1 g of zirconium oxide powder were mixed and ball-milled at 500 rpm for 7 h to obtain a mixed powder;
[0070] (3) The mixed powder was calcined at 450 °C for 3 h, then ball-milled at 150 rpm for 4 h, and sieved to obtain a composite powder with a particle size of 30-50 μm;
[0071] (4) The composite powder is loaded into a mold and first pressed at 15 MPa, and then kept warm and pressurized at a vacuum degree of less than 100 Pa, 750 ° C, and 8 MPa for 9 hours to obtain a high-conductivity lithium phosphate sputtering target for the solid-state battery field.
[0072] Comparative Example 3:
[0073] A lithium phosphate sputtering target material, the specific preparation process is as follows:
[0074] The difference from Example 2 is that there is no modified lithium phosphate powder in the raw material powder. The specific preparation steps are as follows:
[0075] (1) 97 g of lithium phosphate powder, 1 g of niobium oxide powder, 1 g of titanium oxide powder, and 1 g of zirconium oxide powder were mixed and ball-milled at 500 rpm for 7 h to obtain a mixed powder;
[0076] (2) calcining the mixed powder at 450°C for 3 h, then ball milling at 150 rpm for 4 h, sieving to obtain a composite powder with a particle size of 30-50 μm;
[0077] (3) The composite powder is loaded into a mold and first pressed at 15 MPa, and then kept warm and pressurized at a vacuum degree of less than 100 Pa, 750 ° C, and 8 MPa for 9 hours to obtain a high-conductivity lithium phosphate sputtering target for the solid-state battery field.
[0078] Comparative Example 4:
[0079] A lithium phosphate sputtering target material, the specific preparation process is as follows:
[0080] The difference from Example 2 is that the mixed powder is directly pressed into shape. The specific preparation steps are as follows:
[0081] (1) Dissolve 2.5 g of graphene oxide in 500 ml of ethanol, and after ultrasonic homogenization, obtain a graphene oxide dispersion. Then add 25 g of ferric chloride hexahydrate, 13 g of sodium acrylate, and 40 g of sodium acetate. After stirring evenly, react at 200 ° C for 22 h, centrifuge, filter, wash, and dry to obtain magnetic graphene oxide.
[0082] (2) 2.3 g of magnetic graphene oxide was dissolved in 700 ml of ethanol and homogenized by ultrasonication to obtain a magnetic graphene oxide dispersion. Then, 0.75 g of LiOH and 1.2 g of NH 4 H 2 PO 4 , diluted with water, after ultrasonic dispersion, the obtained solution was transferred into a polytetrafluoroethylene reactor, reacted at 190°C for 17 h, centrifuged, filtered, washed, freeze-dried, kept warm at 700°C in an argon atmosphere for 9 h, and crushed to obtain modified lithium phosphate powder;
[0083] (3) 94.5 g of lithium phosphate powder, 2.5 g of modified lithium phosphate powder, 1 g of niobium oxide powder, 1 g of titanium oxide powder, and 1 g of zirconium oxide powder were mixed, and ball-milled at 500 rpm for 7 h to obtain a mixed powder, and then ball-milled at 150 rpm for 4 h, and sieved to obtain a mixed powder with a particle size of 30-50 μm;
[0084] (5) The mixed powder is loaded into a mold and first pressed at 15 MPa, and then kept warm and pressurized at a vacuum degree of less than 100 Pa, 750 ° C, and 8 MPa for 9 hours to obtain a high-conductivity lithium phosphate sputtering target for the solid-state battery field.
[0085] Comparative Example 5:
[0086] A lithium phosphate sputtering target material, the specific preparation process is as follows:
[0087] (1) 97 g of lithium phosphate powder, 1 g of niobium oxide powder, 1 g of titanium oxide powder, and 1 g of zirconium oxide powder were mixed, and ball-milled at 500 rpm for 7 h to obtain a mixed powder, and then ball-milled at 150 rpm for 4 h, and sieved to obtain a mixed powder with a particle size of 30-50 μm;
[0088] (3) The mixed powder is loaded into a mold and first pressed at 15 MPa, and then kept warm and pressurized at a vacuum degree of less than 100 Pa, 750 ° C, and 8 MPa for 9 hours to obtain a high-conductivity lithium phosphate sputtering target for the solid-state battery field.
[0089] Performance Testing
[0090] The performance tests were performed on the composite powders obtained in the examples and comparative examples:
[0091] Fluidity: The test was conducted using a Hall flow meter, and the test results are shown in Table 1;
[0092] The samples obtained from the embodiments and comparative examples were tested for performance:
[0093] Density: obtained by drainage method, the test results are shown in Table 1;
[0094] Resistivity: The four-probe method was used for testing. The test results are shown in Table 1.
[0095] Table 1 Performance test results
[0096]
[0097] From the data analysis, it can be seen from Examples 1-3 in Table 1 that the high-conductivity lithium phosphate sputtering target for solid-state batteries of the present invention has excellent sphericity, and the powder fluidity and loose density can reach a relatively excellent level; and the target density can reach 99.7%, and the resistivity is not higher than 0.08Ω·cm.
[0098] It can be seen from Example 2 and Comparative Examples 1 and 3 in Table 1 that, in the present invention, by adding magnetic graphene oxide to the raw material, on the one hand, the magnetic graphene oxide has excellent electrical conductivity, which can improve the conductivity of the target material to a certain extent. At the same time, compared with traditional graphene oxide, the magnetic graphene oxide has magnetism, which can promote the directional arrangement of the powder, thereby making the raw material powder more evenly distributed during the mixing process; on the other hand, after the magnetic graphene oxide is added to the raw material powder, it can be used as a binder in the subsequent calcination, so that the raw material powders are more closely combined, thereby improving the sphericity of the composite powder, thereby improving the density and electrical conductivity of the target material.
[0099] It can be seen from Example 2 and Comparative Example 2 in Table 1 that, compared with directly adding magnetic graphene oxide, the present invention mixes magnetic graphene oxide with the raw material by doping, which can make the magnetic graphene oxide more evenly dispersed, form a more uniform conductive network, and form a more stable interface bonding, thereby improving the density and conductive performance of the target material.
[0100] It can be seen from Example 2 and Comparative Example 4 in Table 1 that after the mixed powder is calcined, the magnetic graphene oxide doped between the raw materials can be used as a binder while ensuring its own properties, so that the raw material powders are more tightly and stably combined, the sphericity of the composite powder is improved, and then the density of the target material is improved.
[0101] It can be seen from Example 2 and Comparative Example 5 in Table 1 that the present invention dopes magnetic graphene oxide into the raw material and then performs calcination, which together improves the sphericity of the composite powder and further improves the density and conductivity of the target material.
[0102] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for preparing a highly conductive lithium phosphate sputtering target for solid-state batteries, characterized in that: The following steps are involved: (1) mixing lithium phosphate powder, modified lithium phosphate powder, niobium oxide powder, titanium oxide powder and zirconium oxide powder, and performing a ball milling process to obtain a mixed powder; (2) calcining the mixed powder at 300-600°C for 2-4h, performing secondary ball milling, and sieving to obtain a composite powder; (3) The composite powder is loaded into a mold, pressed into shape, and then sintered to obtain a highly conductive lithium phosphate sputtering target for solid-state batteries; The preparation steps of the modified lithium phosphate powder in step (1) are as follows: S1: dissolving graphene oxide in ethanol, and obtaining a graphene oxide dispersion after ultrasonic homogenization, then adding ferric chloride hexahydrate, sodium acrylate, and sodium acetate, stirring evenly, reacting at 180-220°C for 20-24h, and obtaining magnetic graphene oxide after purification; S2: dissolving magnetic graphene oxide in ethanol, homogenizing by ultrasonic treatment to obtain a magnetic graphene oxide dispersion, then adding a lithium source and a phosphorus source, and reacting at 180-200°C for 15-18 h after ultrasonic dispersion, and obtaining a modified lithium phosphate powder after purification, sintering, and crushing; The weight ratio of graphene oxide, ferric chloride hexahydrate, sodium acrylate and sodium acetate in step S1 is 2-3:20-30:10-15:30-50; The weight ratio of the magnetic graphene oxide, the phosphorus source and the lithium source in step S2 is 2-2.5:0.7-0.8:1.15-1.
2.
2. The method for preparing a highly conductive lithium phosphate sputtering target for solid-state batteries according to claim 1, characterized in that: The ball milling speed of the first ball milling in step (1) is 400-600 rpm, and the ball milling time is 6-8 h.
3. The method for preparing a highly conductive lithium phosphate sputtering target for solid-state batteries according to claim 1, characterized in that: The weight percentages of the lithium phosphate powder, modified lithium phosphate powder, niobium oxide powder, titanium oxide powder and zirconium oxide powder in step (1) are 91%-97.91%: 2%-3%: 0.03%-2%: 0.03%-2%:0.03%-2%。 4. The method for preparing a highly conductive lithium phosphate sputtering target for solid-state batteries according to claim 1, characterized in that: The ball milling speed of the secondary ball milling in step (2) is 100-200 rpm, and the ball milling time is 3-5 h.
5. The method for preparing a highly conductive lithium phosphate sputtering target for solid-state batteries according to claim 1, characterized in that: The particle size of the composite powder after sieving in step (2) is 30-50 μm.
6. The method for preparing a highly conductive lithium phosphate sputtering target for solid-state batteries according to claim 1, characterized in that: The pressure of the pressing molding in step (3) is 5-20 MPa.
7. The method for preparing a highly conductive lithium phosphate sputtering target for solid-state batteries according to claim 1, characterized in that: The sintering in step (3) is carried out under vacuum degree <100pa, 500-950°C, 1-10Mpa, and heat and pressure maintenance for 2-3h.
8. The method for preparing a highly conductive lithium phosphate sputtering target for solid-state batteries according to claim 1, characterized in that: In step S2, the phosphorus source is one of H3PO4 and NH4H2PO4, and the lithium source is one of LiOH and Li3PO4.
9. The method for preparing a highly conductive lithium phosphate sputtering target for solid-state batteries according to claim 1, characterized in that: The sintering in step S2 is carried out in an argon atmosphere at 400-900° C. for 8-10 hours.
10. A highly conductive lithium phosphate sputtering target for solid-state batteries, characterized in that: The highly conductive lithium phosphate sputtering target material for the solid-state battery field is prepared according to the preparation method of the highly conductive lithium phosphate sputtering target material for the solid-state battery field according to any one of claims 1 to 9.
Citation Information
Cited By
Direct current sputtering lithium phosphate target material, preparation method and application
CN122484699A
